Effects of Mix Design and Fracture Energy on Transverse Cracking Performance of Asphalt Pavements in Minnesota. Issue 1 (2016) - Dave, Eshan V.; Hoplin, Chelsea; Helmer, Benjamin; Dailey, Jay; Van Deusen, David; Geib, Jerry; Dai, Shongtao; Johanneck, Luke
Asphalt pavements in colder climates encounter significantly shortened service lives because of excessive transverse cracking. This paper presents the results for 26 pavement sections in Minnesota that were studied to evaluate the effects of asphalt mix designs on pavement cracking performance. The field performance is presented with various cracking measures and compared with mix design aspects such as amount of asphalt binder, binder grade, and amount of recycling. The disk-shaped compact tension (DCT) fracture energies measured on the field cored samples are also compared with cracking performance. In this study, asphalt pavement sections from several locations were evaluated to encompass various types of asphalt mixtures and asphalt construction types that were commonly used in Minnesota. The amount of transverse cracking for each section was converted into a newly proposed cracking performance measure that accounted for the amount, rate, and timing of cracking. The comparisons between asphalt mixture attributes and cracking performance measures showed that the amounts of total asphalt binder and recycled asphalt binder may not be sufficient. Performance testing, in addition to currently used controls (mix volumetrics and constituent properties), is recommended to ensure good cracking performance. The DCT fracture energy results for companion sections show that mixtures with higher fracture energies exhibit lower amounts of transverse cracking.